Vasodilating prostaglandins attenuate ischemic renal injury only if thromboxane is inhibited. - Klausner, J M (1989)
Ischemia-induced renal injury is prevented by inhibition of thromboxane (Tx) synthesis. This protection was believed to be secondary to a high prostaglandin (PG)/TxA2 ratio. This study tests whether increasing the PG/Tx ratio by administration of vasodilating PGs protects the reperfused ischemic kidney. Anesthetized rats underwent right nephrectomy and 45 minutes of left renal pedicle clamping. Beginning 10 minutes before clamp release, animals were treated intravenously with the following: saline placebo (n = 10); the cyclooxygenase inhibitor ibuprofen (Ibu), 12.5 mg/Kg in a bolus (n = 8); a stable analogue of prostacyclin (PGI2), 500 ng/kg/minute for 2 hours (n = 9); PGE1, 400 ng/kg/minute for 2 hours (n = 8); the combination Ibu and PGI2 (n = 8) or PGE1 (n = 8). In saline treated ischemic controls, 5 minutes after reperfusion plasma, thromboxane (TxB2) and 6-keto-PGF1 levels were 2537 and 317 pg/ml, respectively--higher than the TxB2 and 6-keto-PGF1 levels of 750 and 80 pg/ml, respectively, in nephrectomized but nonischemic sham controls (n = 7) (p less than 0.05). In ischemic control animals at 24 hours, creatinine levels were 4.6 mg/dl, relative to 0.9 ml/dl in sham animals (p less than 0.05); the weight of the left (L) ischemic kidney relative to the right (R) normal kidney was 118%, compared with 99% in sham animals (p less than 0.05); and renal histology of ischemic control animals at 24 hours showed acute tubular necrosis (ATN) relative to normal findings in sham animals. Pretreatment with Ibu led to: TxB2 and 6-keto-PGF1 levels of 116 and 40 pg/ml, lower than those of sham animals (p less than 0.05); creatinine levels of 4.6 mg/dl, L/R renal weight of 119%; and ATN similar to that of ischemic controls. Treatment with a PGI2 analogue or PGE1 was not protective and led to increases in TxB2, 6-keto-PGF1, creatinine, L/R renal weight, and ATN similar to that of ischemic controls. The combination of Ibu and either PGI2 or PGE1 led to: reduced levels of TxB2 and 6-keto-PGF1 (p less than 0.05); attenuated increases in creatinine to 2.2 and 2.3 mg/dl, respectively (p less than 0.05); and limited ATN (p less than 0.05). These data indicate that the vasodilating PG protect the ischemic reperfused kidney only when Tx is inhibited.